Activity and safety of temozolomide in advanced adrenocortical carcinoma patients. Issue 6 (December 2019) - Cosentini, Deborah; Badalamenti, Giuseppe; Grisanti, Salvatore; Basile, Vittoria; Rapa, Ida; Cerri, Sara; Spallanzani, Andrea; Perotti, Paola; Musso, Emanuela; Laganà, Marta; Ferrari, Vittorio D; Luppi, Gabriele; et al.
Abstract : Objective: Temozolomide has shown a significant anti-proliferative activity on adrenocortical cancer (ACC) cells in vitro . Design: On the basis of these results the drug was prescribed as second/third line in advanced metastatic ACC patients in four referral centers in Italy. Methods: We retrospectively collected anagraphic, clinical and pathological data of patients with advanced ACC with disease progression to standard chemotherapy plus mitotane who were treated with temozolomide at the dose of 200 mg/m 2 /die given for 5 consecutive days every 28 days. The primary endpoint was the disease control rate, defined as objective response or disease stabilization after 3 months. Secondary endpoints were overall survival (OS), progression-free survival (PFS) and drug safety. Results: Twenty-eight patients have been included in the study. Ten patients (35.8%, 95% CI: 17.8–53.8) obtained a disease control from temozolomide treatment. In particular, 1 patient had a complete response, 5 patients a partial response and 4 patients stable disease. Median PFS was 3.5 months and median OS was 7.2 months. Disease response was more frequently observed in patients with methylation of O6-methylguanine-DNA methyltransferase (MGMT) gene. Temozolomide therapy was well tolerated and most toxicities were limited to grade G1–2 according to WHO criteria. Conclusion: Temozolomide was found active in the management of advanced ACC patients. The disease control rate obtained, however, was short-lived and the prognosis of treated patients was poor.